2004
DOI: 10.5194/angeo-22-4077-2004
|View full text |Cite
|
Sign up to set email alerts
|

Studies of medium scale travelling ionospheric disturbances using TIGER SuperDARN radar sea echo observations

Abstract: Abstract. Seasonal and diurnal variations in the direction of propagation of medium-scale travelling ionospheric disturbances (MSTIDs) have been investigated by analyzing sea echo returns detected by the TIGER SuperDARN radar located in Tasmania (43.4 • S, 147.2 • E geographic; −54.6 • ). A strong dependency on local time was found, as well as significant seasonal variations. Generally, the propagation direction has a northward (i.e. equatorward) component. In the early morning hours the direction of propagati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 30 publications
(38 reference statements)
6
50
0
Order By: Relevance
“…Recently, MSTIDs have been studied statistically in many places worldwide using various techniques (Frissell et al 2014(Frissell et al , 2016Fukushima et al 2012;Grocott et al 2013;He et al 2004;Ichihara et al 2013;Ishida et al 2008;Klausner et al 2009;Kotake and Otsuka 2007;Medvedev et al 2013;Oinats et al 2015Oinats et al , 2016Otsuka et al 2011Otsuka et al , 2013Shiokawa et al 2003Shiokawa et al , 2009. In this study, we present observations of MSTIDs' horizontal velocities over Taiwan using HF Doppler sounding.…”
Section: Introductionmentioning
confidence: 91%
“…Recently, MSTIDs have been studied statistically in many places worldwide using various techniques (Frissell et al 2014(Frissell et al , 2016Fukushima et al 2012;Grocott et al 2013;He et al 2004;Ichihara et al 2013;Ishida et al 2008;Klausner et al 2009;Kotake and Otsuka 2007;Medvedev et al 2013;Oinats et al 2015Oinats et al , 2016Otsuka et al 2011Otsuka et al , 2013Shiokawa et al 2003Shiokawa et al , 2009. In this study, we present observations of MSTIDs' horizontal velocities over Taiwan using HF Doppler sounding.…”
Section: Introductionmentioning
confidence: 91%
“…Livneh et al (2007) used incoherent scatter radar at Arecibo Observatory to observe quasi-coherent continuous waves with periods of ∼1 h in the ionosphere. These are also typical periods of auroral AGWs (Bristow and Greenwald, 1997) that are likely generated by pulsed ionospheric convection (Prikryl et al, 2005) virtually continuously and sometimes observed as TIDs by SuperDARN He et al, 2004). If auroral medium scale AGWs are observed in the ionosphere above Arecibo they must be ducted through the lower atmosphere waveguide and leak back to thermosphere; otherwise they would be damped and dissipate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ground backscatter echoes, there are also echoes backscattered directly by ionospheric irregularities. Separation between the two echo types is performed in the standard way (He et al 2004). …”
Section: Instrumentation and Analysis Methodsmentioning
confidence: 99%
“…A number of papers presenting statistical studies of TIDs have been published in the last 15 years (Afraimovich et al 1999(Afraimovich et al , 2000Ding et al 2008;Kotake et al 2007;Medvedev et al 2013;Otsuka et al 2011;Shiokawa et al 2003;Tsugawa et al 2004). There are also statistical studies that utilized SuperDARN radar data (Bristow et al 1996;He et al 2004;Ichihara et al 2013;Ishida et al 2008;Grocott et al 2013). Apparently, a relatively small number of such studies are related to the complexity of extensive dataset processing, as well as the issues concerning an automated interpretation of HF radar data.…”
Section: Introductionmentioning
confidence: 99%